Optimized Protocol for OnGuard2 Software in Studying Guard Cell Membrane Transport and Stomatal Physiology - Shafaque, Sehar; Ma, Yue; Rui, Mengmeng; He, Bingqing; Zhu, Ziyi; Cao, Fangbing; Wu, Feibo; Wang, Yizhou (Frontiers in Plant Science, 2020)
Stomata are key innovation in plants to drive the global carbon and water cycle. In the past few decades, many stomatal models were developed for studying gas exchange, photosynthesis, and transpirational characteristics of plants, but they provided limited information on stomatal mechanisms at molecular and cellular levels. The quantitative mathematical modelling offers an effective in silico approach to explore the link between microscopic transporter function and the macroscopic stomatal characteristics. As the first step, a dynamic system model based on the guard cell membrane transport system was developed and encoded in the OnGuard software. This software has already generated a wealth of predictions and outcomes sufficient to guide phenotypic and mutational studies. It has a user-friendly interface, which can be easily accessed by researchers to manipulate the key elements and parameters in the system for guard cell simulation. To promote the OnGuard application, we outline here a standard protocol that will enable users with basic plant physiology, cell biology, and membrane transport experience to advance quickly in using it.